2016
DOI: 10.1155/2016/5149825
|View full text |Cite
|
Sign up to set email alerts
|

Association between Stable Coronary Artery Disease and In Vivo Thrombin Generation

Abstract: Background. Thrombin has been implicated as a key molecule in atherosclerotic progression. Clinical evidence shows that thrombin generation is enhanced in atherosclerosis, but its role as a risk factor for coronary atherosclerotic burden has not been proven in coronary artery disease (CAD) stable patients. Objectives. To evaluate the association between TAT levels and homocysteine levels and the presence of coronary artery disease diagnosed by coronary angiography in patients with stable CAD. Methods and Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Additionally, thrombin has been shown to augment levels of mRNA that encode monocyte chemoattractant protein 1, a well-characterized chemokine, abundant in human atherosclerotic plaques. 55 In fact, thrombin is a central coagulation protease. It is known to promote numerous pro-atherogenic actions in vitro such as activation of protease-activated receptor 1, endothelial permeability, migration and proliferation of vascular smooth muscle cells, platelet activation, leukocyte adhesion and recruitment, cytokine and chemokine production, vascular calcification, angiogenesis, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, thrombin has been shown to augment levels of mRNA that encode monocyte chemoattractant protein 1, a well-characterized chemokine, abundant in human atherosclerotic plaques. 55 In fact, thrombin is a central coagulation protease. It is known to promote numerous pro-atherogenic actions in vitro such as activation of protease-activated receptor 1, endothelial permeability, migration and proliferation of vascular smooth muscle cells, platelet activation, leukocyte adhesion and recruitment, cytokine and chemokine production, vascular calcification, angiogenesis, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed the expression profile of APOLs in a model of endothelial cells (HMEC-1) in response to TNF-α and IFN-γ. We extended our observations to other inflammatory stimuli involved in cardiovascular diseases: oxLDL and MoxLDL, two pro-atherogenic molecules [29], thrombin a serine protease linking coagulation and inflammation [30], and myeloperoxidase an enzyme released by neutrophils at inflammation sites [29]. We analyzed the functional role of one of the family members in the endothelial phenotype.…”
Section: Discussionmentioning
confidence: 81%
“…This pro-atherogenic effect may be further accelerated when traditional atherogenic risk factors are present. Moreover, the FVL-related hypercoagulability may induce a higher risk of clot formation on the unstable plaque [ [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] ]. However, the interaction analyses rely on a lower number of subjects because of the combination of multiple risk factors, hence, their results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%